Multicenter evaluation of the Panbio™ COVID-19 rapid antigen-detection test for the diagnosis of SARS-CoV-2 infection. (May 2021) - Merino, Paloma; Guinea, Jesús; Muñoz-Gallego, Irene; González-Donapetry, Patricia; Galán, Juan Carlos; Antona, Nerea; Cilla, Gustavo; Hernáez-Crespo, Silvia; Díaz-de Tuesta, José Luis; Gual-de Torrella, Ana; González-Romo, Fernando; Escribano, Pilar; et al.
Abstract: Objectives: The standard RT-PCR assay for coronavirus disease 2019 (COVID-19) is laborious and time-consuming, limiting testing availability. Rapid antigen-detection tests are faster and less expensive; however, the reliability of these tests must be validated before they can be used widely. The objective of this study was to determine the performance of the Panbio™ COVID-19 Ag Rapid Test Device (PanbioRT) (Abbott) in detecting severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in nasopharyngeal swab specimens. Methods: This prospective multicentre study was carried out in ten Spanish university hospitals and included individuals with clinical symptoms or epidemiological criteria of COVID-19. Only individuals with ≤7 days from the onset of symptoms or from exposure to a confirmed case of COVID-19 were included. Two nasopharyngeal samples were taken to perform the PanbioRT as a point-of-care test and a diagnostic RT-PCR test. Results: Among the 958 patients studied, 325 (90.5%) had true-positive results. The overall sensitivity and specificity for the PanbioRT were 90.5% (95%CI 87.5–93.6) and 98.8% (95%CI 98–99.7), respectively. Sensitivity in participants who had a threshold cycle ( C T ) < 25 for the RT-PCR test was 99.5% (95%CI 98.4–100), and in participants with ≤5 days of the clinical course it was 91.8% (95%CI 88.8–94.8). Agreement between techniques was 95.7% (κ score 0.90; 95%CI 0.88–0.93). Conclusions: The PanbioRT performs well clinically, with even more reliable results for patients with a shorter clinical course of the disease or a higher viral load. The results must be interpreted based on the local epidemiological context.